Brief Report: Excitatory and Inhibitory Brain Metabolites as Targets of Motor Cortex Transcranial Direct Current Stimulation Therapy and Predictors of Its Efficacy in Fibromyalgia1. Issue 2 (February 2015) - Foerster, Bradley R.; Nascimento, Thiago D.; DeBoer, Misty; Bender, Marycatherine A.; Rice, Indie C.; Truong, Dennis Q.; Bikson, Marom; Clauw, Daniel J.; Zubieta, Jon‐Kar; Harris, Richard E.; DaSilva, Alexandre F.
<x xml:space="preserve">Abstract</x> Objective Transcranial direct current stimulation (tDCS) has been shown to improve pain symptoms in fibromyalgia (FM), a central pain syndrome whose underlying mechanisms are not well understood. This study was undertaken to explore the neurochemical action of tDCS in the brain of patients with FM, using proton magnetic resonance spectroscopy (1H‐MRS). Methods Twelve patients with FM underwent sham tDCS over the left motor cortex (anode placement) and contralateral supraorbital cortex (cathode placement) for 5 consecutive days, followed by a 7‐day washout period and then active tDCS for 5 consecutive days. Clinical pain assessment and 1H‐MRS testing were performed at baseline, the week following the sham tDCS trial, and the week following the active tDCS trial. Results Clinical pain scores decreased significantly between the baseline and active tDCS time points (P = 0.04). Levels of glutamate + glutamine (Glx) in the anterior cingulate were significantly lower at the post–active tDCS assessment compared with the post–sham tDCS assessment (P = 0.013), and the decrease in Glx levels in the thalami between these time points approached significance (P = 0.056). From baseline to the post–sham tDCS assessment, levels of N‐acetylaspartate (NAA) in the posterior insula increased significantly (P = 0.015). There was a trend toward increased levels of γ‐aminobutyric acid (GABA) in the anterior insula after active tDCS, compared with baseline (P = 0.064). Baseline anterior cingulate Glx levels correlated significantly with changes in pain score, both for the time period from baseline to sham tDCS (β1 = 1.31, P < 0.001) and for the time period from baseline to active tDCS (β1= 1.87, P < 0.001). Conclusion The present findings suggest that GABA, Glx, and NAA play an important role in the pathophysiology of FM and its modulation by tDCS.